Socialno delo v uresničevanju idealov pravične družb - Šugman Bohinc, Lea (Socialno delo, 2016)
The article resonds to questions such as: how do we cope with the characteristic splits of contemporary social work, such as theory and practice, direct and indirect practice? How is the global standard of multiculturalism realised in higher education, research and practice of social work? How can we create stimulative conditions to develop a culture of co-existence that will embody ideals of multiculturality, global citizenship etc. in a more just society? The article argues for epistemologically reflexive, ethically sensitive and (self)critical attitude as well as narrative skills of collaboration in education, research and constructive dialogical practice of social work with individuals, families and groups as well as communities and systems of administration and social policy.
Keywords: social work; socialno delo; theory; complexity; pravična družba; multiculturality; večkulturnost; global standards; globalni standardi; narativna praksa; narrative practice; visokošolsko izobraževanje